"Catastrophic" pathways to smoking cessation: findings from national survey. Issue 7539 (27th January 2006) - West, Robert; Sohal, Taj
Abstract: Objective To assess the extent to which the prevailing model of smoking cessation (that smokers typically prepare their attempts to stop smoking in advance and that doing so increases their chances of success) is correct. Design Cross sectional household survey. Setting England. Participants 918 smokers who reported having made at least one quit attempt and 996 ex-smokers aged 16 and over. Main outcome measures Whether the most recent quit attempt was planned in advance and whether quit attempts made at least six months before resulted in at least six months' abstinence. Results 48.6% of smokers reported that their most recent quit attempt was put into effect immediately the decision to quit was made. Unplanned quit attempts were more likely to succeed for at least six months: among respondents who had made a quit attempt between six months and five years previously the odds of success were 2.6 times higher (95% confidence interval 1.9 to 3.6) in unplanned attempts than in planned attempts; in quit attempts made 6-12 months previously the corresponding figure was 2.5 (1.4 to 4.7). The differences remained after controlling for age, sex, and socioeconomic group. Conclusions A model of the process of change based on "catastrophe theory" is proposed, in which smokers have varying levels of motivational "tension" to stop and then "triggers" in the environment result in a switch in motivational state. If that switch involves immediate renunciation of cigarettes, this can signal a more complete transformation than if it involves a plan to quit at some future point.